معاصر عائلی مسائل کے عوامل و اثرات اور تدارک: شریعت اسلامیہ کے تناظر میں پاکستانی سماج کا مطالعہ: FACTORS AND EFFECTS OF CONTEMPORARY FAMILY ISSUES AND THEIR REMEDIES: A STUDY OF PAKISTANI SOCIETY IN THE CONTEXT OF ISLAMIC SHARIAH - Dr Irfan Jafar; Hafiz Muhammad Usman; Asia Parveen (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The people of the present era have accumulated the comforts of life, yet every individual is still plagued by various problems and anxieties. One significant reason for this is the destabilization of the fundamental unit of society, the "family system," from its roots. Regardless of where a person resides in the world, their center and focal point are naturally their home and family. Among the various institutions of the state, the family is the primary and foundational institution. It plays a vital role in the education and upbringing of future generations. The high and stable moral values of a family contribute significantly to the social stability and development. That is, the strength of society and the stability of the family are based on individual upbringing within the household. In the present age, where humanity is witnessing a decline in ethical and social values, the teachings of the Prophet Muhammad (peace be upon him) are needed for the resolution of many issues. Similarly, the reform of the family system holds the same importance in the teachings of the Prophet Muhammad (peace be upon him) as a guiding light. This is the remedy that encompasses the solution to every ailment. The foundation of Pakistan’s family system is based on our religion and historical heritage. Several factors contribute to the construction of our family system, including regional, economic, cultural, and historical traditions, which hold significant importance. However, it is also a reality that many factors and catalysts continuously impact the structure and functions of the family system over time, leading to changes and transformations within family institutions. The article titled Factors and Effects of Contemporary Family Issues and their Remedies: A Study of Pakistani Society in the Context of Islamic Shariah explores the causes, factors, and catalysts contributing to the disruption of the family system in contemporary life. It also suggests remedies for addressing these issues in light of Islamic Shariah, aiming to establish a strong and exemplary society by implementing key recommendations.